Cell-Free Whey from Milk Fermented with Bifidobacterium breve C50 Used to Modify the Colonic Microflora of Healthy Subjects - Romond, Marie-Bénédicte; Ais, Assia; Guillemot, François; Bounouader, Rachid; Cortot, Antoine; Romond, Charles (Journal of dairy science, 1998)
The ingestion of viable bacteria is thought to be required to modify intestinal microflora. In the present study, the effects on fecal flora of consumption of cell-free concentrated whey from milk that had been fermented with Bifidobacterium breve C50 was tested using 10 healthy human volunteers. Results were compared with effects of a commercial milk formula that had been fermented with Streptococcus thermophilus and B. breve C50 and given to 10 control subjects. Nitroreductase and β-glucuronidase activities were assessed as risk indexes for colon carcinogenesis, and β-galactosidase was measured as an indicator of the fermentation capacity of the colonic flora. Fecal excretion of Bacteroides fragilis, Clostridium perfringens, and clostridial spores decreased after 7 d of consumption of either preparation; however, counts of bifidobacteria only increased after intake of B. breve whey. Fecal pH was reduced from 7.1±0.2 to 6.6±0.3 after intake of whey that had been fermented with Bif. breve. Fecal nitroreductase and β-glucuronidase significantly decreased, and β-galactosidase activity increased, after consumption of either preparation. The results indicate that ingestion of viable bifidobacteria was not required to modify intestinal flora of humans. Repression of B. fragilis and clostridia seems to be independent of colonic bifidobacterial overgrowth in humans.